2019
DOI: 10.1177/1087054719855685
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Nonpharmacological Treatments on Comorbid Internalizing Symptoms of Adults With Attention-Deficit/Hyperactivity Disorder: A Meta-Analytic Review

Abstract: Background: Attention-deficit/hyperactivity disorder (ADHD) is highly comorbid in adulthood. This meta-analysis was aimed at ascertaining the efficacy of different psychotherapies in improving comorbid internalizing symptoms in adults with ADHD. Method: Twenty randomized controlled trials and 12 uncontrolled pretest–posttest studies were included and combined using the inverse variance method. Risk of bias and heterogeneity assessment and moderator analyses were performed. Results: Cognitive-behavioral therapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 155 publications
(224 reference statements)
10
17
1
Order By: Relevance
“…Our results revealed that CBT improved comorbid depression, and/or anxiety, and/or ED in adults with ADHD when testing at post-treatment and follow-up, and when the outcomes were evaluated by the patients themselves or an independent observer. These findings are in line with previous meta-analyses studies of adults with ADHD (Jensen et al, 2016;Lopez et al, 2018;López-Pinar et al, 2020), which consistently supported the efficacy of CBT in improving comorbid emotional symptoms (i.e., depression, anxiety, and ED). However, we did not detect the efficacy of CBT in alleviating the emotional symptoms in children with ADHD.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Our results revealed that CBT improved comorbid depression, and/or anxiety, and/or ED in adults with ADHD when testing at post-treatment and follow-up, and when the outcomes were evaluated by the patients themselves or an independent observer. These findings are in line with previous meta-analyses studies of adults with ADHD (Jensen et al, 2016;Lopez et al, 2018;López-Pinar et al, 2020), which consistently supported the efficacy of CBT in improving comorbid emotional symptoms (i.e., depression, anxiety, and ED). However, we did not detect the efficacy of CBT in alleviating the emotional symptoms in children with ADHD.…”
Section: Discussionsupporting
confidence: 91%
“…Finally, another important finding was that publication bias indicators were found only for ED in post-treatment of adults with ADHD. The rest of the outcomes were free from publication bias in studies including children and adults with ADHD, thus supporting the validity of the results, which is consistent with recent meta-analysis works (Lopez et al, 2018;López-Pinar et al, 2020).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Since ED may significantly influence the development of children and adolescents, effective and available treatment is of utmost importance. Psychotherapy may be divided into four groups: (i) Dialectic Behavioral Therapy [reviewed by Courtney-Seidler et al ( 430 )], (ii) Behavioral and Cognitive Behavioral Therapy (including Schema Therapy) [recently reviewed by López-Pinar et al ( 431 )] in adults, (iii) multimodal treatment (including, e.g., parental interventions, pharmacotherapy, and others), (iv) other therapies, such as analytic group therapy, hypnotherapy, neurofeedback, and others.…”
Section: Resultsmentioning
confidence: 99%